Spooktacular Halloween [videorecording (DVD)] ([Publisher not identified], 2015)
From carving pumpkins to creating scary costumes to trick or treating, PBS Kids friends really know how to celebrate Halloween in these five 'spooktacular' adventures, featuring Halloween stories from these five shows: WordWorld ; Caillou ; Peg + Cat ; Dinosaur Train ; WordGirl.